The Interrelation of Phenomenology, Social Sciences and the Arts
VII, 331 p. 6 illus.
Keywords: This book features papers written by renowned international scholars that analyze the interdependence of art, phenomenology, and social science. The papers show how the analysis of the production as well as the perception and interpretation of art work needs to take into consideration the subjective viewpoint of the artist in addition to that of the interpreter. Phenomenology allows a description of the subjectively centered life-world of the individual actor—artist or interpreter—and the objective structures of literature, music, and the aesthetic domain in general. The perspective of social science serves to reconstruct the socio-historical structure involved in the creation and reception of the art work. The authors concentrate on this specific theoretical focus which combines both phenomenology and social science and offers an innovative framework for the analysis of works of art from the fields of literature, music, visual arts, photography, and film. Some of the contributions present creative interpretations of a variety of distinct art works in addition to the realization of theoretical reflections on the interdependence of arts, phenomenology, and social science. This book features papers that were presented at the international and interdisciplinary conference Phenomenology, Social Sciences, and the Arts, held at the University of Konstanz, May 2009, in commemoration of philosopher and social scientist Alfred Schutz, the developer of phenomenologically oriented sociology. It will appeal to researchers, scholars, and students in phenomenology, social sciences, art theory, and the arts. .